The Mediating Role of Catastrophizing in the Relationship Between Emotional Clarity and Posttraumatic Stress Symptoms Among Earthquake Survivors in Korea: A Cross-Sectional Study - Kwon, Ha Rin; Eoh, Yookyung; Park, Soo Hyun (Frontiers in Psychology, 2020)
Difficulties in emotion regulation reportedly contribute to the development and maintenance of PTSD following exposure to natural disasters. Based on the extended process model of emotion regulation, the present study hypothesized that maladaptive emotion regulation strategies will mediate the relationship between emotional clarity and posttraumatic stress symptoms in a sample of earthquake survivors. A total of 195 adult residents of Gyeongju and Pohang, southeastern coastal cities in Korea who had experienced recent earthquakes participated in an online survey study. They completed questionnaires assessing emotional clarity, emotion regulation and posttraumatic stress symptoms one-year and 10 months after the Gyeongju earthquake, and 7 months after the Pohang earthquake. Bootstrapping procedures were used to test for a mediation effect. The results suggest that emotional clarity was indirectly associated with posttraumatic stress symptoms through maladaptive emotion regulation strategies, especially catastrophizing. Findings suggest that individuals with low emotional clarity tend to use maladaptive strategies, catastrophizing in particular, which may contribute to posttraumatic stress symptoms. This may reflect the mechanism underlying emotional clarity and offer suggestions for target of treatment in the management of long-term psychological difficulties in earthquakes survivors.